The impact of gender on outcomes of patients with ST elevation myocardial infarction transported for percutaneous coronary intervention: analysis of the PRAGUE-1 and 2 studies. Issue 3 (10th August 2007) - Motovska, Z; Widimsky, P; Aschermann, M
Abstract : Background: Data comparing survival outcomes for women versus men transported for pPCI were absent. Objectives: To assess the impact of gender on 30-day mortality of patients with STEMI transported for pPCI. Methods: The data from the PRAGUE-1 and PRAGUE-2 trials were analysed. Studies compared thrombolysis in the community hospital and pPCI after transportation to cardiocentre. A group of 520 patients treated with thrombolysis, and 530 transported for pPCI, were analysed. Results: Women were older, with a higher risk profile. They had longer ischaemia time. Mortality of patients treated with TL was significantly higher in women than in men (15% vs 9%, p = 0.043). There was no significant gender difference in mortality in the PCI group (8.2% of women vs 6.2% of men, p = 0.409). Mortality of women treated with on-site TL was nearly twice as high as mortality of women transported for pPCI (p = 0.043). After adjustment in a multivariate model the odds ratio for mortality in women was 0.74 (95% CI 0.26 to 2.05; p = 0.556). Conclusion: Long-distance transportation of women with STEMI from a community hospital to a tertiary PCI centre is a significantly more effective treatment strategy than on-site TL. Gender did not determine survival in patients transported for pPCI.